A Carpentries Collaboration: Teaching Foundational Coding and Data Science Skills to Researchers - Jackson, Carolyn S. (My University, 2025)
Many researchers, particularly graduate students, lack the skills needed to do computational, data-intensive research. These skills are often not included as a part of basic research training in many disciplines. Carpentries workshops can help fill this need by teaching foundational coding and data science skills to researchers, employing openly available lessons and ‘code with me’ pedagogy. This session will present a case study in how, with the support of the Great Plains Network’s Carpentries Instructors Mentoring, Kansas State University has established a cross-disciplinary community of interest to offer Carpentries Workshops to researchers on campus and with USDA partners.
Keywords: Carpentries Workshops; Coding and data analysis instruction; data literacy